Reporting quality of randomised controlled trial abstracts among high-impact general medical journals: a review and analysis. Issue 7 (28th July 2016) - Hays, Meredith; Andrews, Mary; Wilson, Ramey; Callender, David; O'Malley, Patrick G; Douglas, Kevin
Abstract : Objective: The aim of this study was to assess adherence to the Consolidated Standards of Reporting Trials (CONSORT) for Abstracts by five high-impact general medical journals and to assess whether the quality of reporting was homogeneous across these journals. Design: This is a descriptive, cross-sectional study. Setting: Randomised controlled trial (RCT) abstracts in five high-impact general medical journals. Participants: We used up to 100 RCT abstracts published between 2011 and 2014 from each of the following journals: The New England Journal of Medicine ( NEJM ), the Annals of Internal Medicine ( Annals IM ), The Lancet, the British Medical Journal ( The BMJ ) and the Journal of the American Medical Association ( JAMA ). Main outcome: The primary outcome was per cent overall adherence to the 19-item CONSORT for Abstracts checklist. Secondary outcomes included per cent adherence in checklist subcategories and assessing homogeneity of reporting quality across the individual journals. Results: Search results yielded 466 abstracts, 3 of which were later excluded as they were not RCTs. Analysis was performed on 463 abstracts (97 from NEJM, 66 from Annals IM, 100 from The Lancet, 100 from The BMJ, 100 from JAMA ). Analysis of all scored items showed an overall adherence of 67% (95% CI 66% to 68%) to the CONSORT for Abstracts checklist. The Lancet had the highest overall adherence rate (78%; 95% CI 76% to 80%), whereas NEJM had the lowest (55%; 95% CI 53% to 57%). Adherence rates to 8 of the checklist items differed by >25% between journals. Conclusions: Among the five highest impact general medical journals, there is variable and incomplete adherence to the CONSORT for Abstracts reporting checklist of randomised trials, with substantial differences between individual journals. Lack of adherence to the CONSORT for Abstracts reporting checklist by high-impact medical journals impedes critical appraisal of important studies. We recommend diligent assessment of adherence to reporting guidelines by authors, reviewers and editors to promote transparency and unbiased reporting of abstracts.